Creative Problem Posing Activity (CPPA): A New Approach for Evaluating Creative Thinking Abilities in Mathematics - Koklu, Dr. Onder (International Journal of Scientific Research and Management (IJSRM), 2018)
The purpose of this study is to analyze a new measurement method in the examination of the creative thinking abilities of prospective mathematics teachers. CPPA (Creative Problem Posing Activity) is a method that is revealed with the aim of measuring the creativity of teacher candidates in mathematical problem posing. CPPA has made it possible for the teacher candidates to measure creativity components of individual mathematical creativity (fluency, flexibility, originality) separately by establishing a new scoring scheme. With participating 305 mathematics teacher candidates, this research has revealed the relationship between CPPA performances and TTCT (Torrance Creative Thinking Test) performances of teacher candidates. The findings of the research show a statistically significant relationship between teacher candidates' scores on the Torrance Test of Creative Thinking (TTCT) and their scores on the CPPA.